Odpowiedź :
Odpowiedź:
d) [tex]2x^2+16x=0[/tex]
[tex]2x(x+8)=0[/tex]
[tex]x=0 \vee x=-8[/tex]
e) [tex]4x^2-144=0[/tex]
[tex]4(x^2-36)=0[/tex]
[tex]4(x-6)(x+6)=0[/tex]
[tex]x=6 \vee x=-6[/tex]
f) [tex]x^2+12=0[/tex]
[tex]x^2=-12[/tex]
[tex]x \in \varnothing[/tex]
d]
2x² + 16x = 0 / : 2
x² + 8x =0
x(x + 8) = 0
x = 0 ∨ x + 8 = 0
x = 0 ∨ x = -8
e]
4x² - 144 = 0 / : 4
x² - 36 = 0
(x + 6)(x - 6) = 0
x + 6 = 0 ∨ x - 6 = 0
x = -6 ∨ x = 6
f]
x² + 12 = 0
x² = -12
Sprzeczność, bo żadna liczba rzeczywista podniesiona do parzystej potęgi nie da liczby ujemnej.